The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1097/wno.0000000000000998
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Patient-Reported Outcomes of Visual Field Defects and Compensatory Mechanisms in Patients After Cerebral Hemispherectomy

Abstract: Background: In cases of intractable epilepsy resistant to drug therapy, hemispherectomy is often the only treatment option to mitigate seizures; however, the true long-term subjective visual outcomes are relatively unexplored. In this study, we sought to determine and characterize patientreported visual function years after hemispherectomy. Methods: This was an observational study conducted on a large cohort of children with seizure disorder treated with cerebral hemispherectomy. An online survey was sent to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It is of interest, that the vast majority of these patients developed torticollis from compensating for their visual deficits ( Chen et al, 2019 ). Similarly, Meer et al (2021) reported in their pediatric series that 56 % of their cases had decreased visual acuity after surgery, 71 % experienced new visual field deficits while visual field impairment preexisted in others ( Meer et al, 2021 ). In summary, a postoperative hemianopia is unavoidable in a complete hemispheric disconnection, yet in most cases it will not impair function, and various compensatory mechanisms have been described, so correction (such as treatment of the strabismus) may not be necessary.…”
Section: Complications: An Overview and A Consensus On Their Avoidancementioning
confidence: 92%
See 1 more Smart Citation
“…It is of interest, that the vast majority of these patients developed torticollis from compensating for their visual deficits ( Chen et al, 2019 ). Similarly, Meer et al (2021) reported in their pediatric series that 56 % of their cases had decreased visual acuity after surgery, 71 % experienced new visual field deficits while visual field impairment preexisted in others ( Meer et al, 2021 ). In summary, a postoperative hemianopia is unavoidable in a complete hemispheric disconnection, yet in most cases it will not impair function, and various compensatory mechanisms have been described, so correction (such as treatment of the strabismus) may not be necessary.…”
Section: Complications: An Overview and A Consensus On Their Avoidancementioning
confidence: 92%
“…These symptoms occurred more frequently in dominant hemisphere involvement. Postoperative visual field and/or visual acuity worsening has been demonstrated in pediatric series ( Chen et al, 2019 ; Meer et al, 2021 ). Chen et al (2019) reported that 49 % of their pediatric cases developed de novo or had worsening of their preoperative strabismus.…”
Section: Complications: An Overview and A Consensus On Their Avoidancementioning
confidence: 99%